Motivasi dan Implikasi Budaya Baca Al-Qur’an Terhadap Spiritualitas Kolektif Santri di Pondok Pesantren - Sholeh, Farhanudin; Zainuddin, Zainuddin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
The focus of this study is the motivation and implications of the culture of reciting the Quran on the collective spirituality of students at the Miftahul Ulum Islamic Boarding School in Lumajang. This is a qualitative field-based study with a phenomenological approach. Data collection was conducted using observation, interviews, and documentation methods with the head of the Islamic boarding school, teaching staff, and students. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of the tradition of reciting Surah Yasin at the Miftahul Ulum Islamic Boarding School is an effort to achieve the school’s vision and mission: to shape students’ character, ethics, and social behavior through repeated interaction with the Quranic verses, thereby creating a spiritual and emotional connection with the divine word. This activity plays a crucial role in the formation of Quranic character and discipline, and in increasing students’ religious awareness.